Godaan Seorang Imam dalam Pelayanan menurut Yohanes Krisostomus - Hendi Hendi; Sesilina Gulo (Sekolah Tinggi Teologi Intheos Surakarta, 2021)
Abstract. This article discussed how a priest (church elder or overseer) can overcome worldly temptations through three spiritual disciplines or ascesis: prayer, fasting, and inner guarding. This article used the analytical and argumentative methods in literature written by John Chrysostom in his book